IMPACT OF TRANSCULTURAL NURSING-BASED CULTURE AND LIFESTYLE ON THE SUCCESS OF EXCLUSIVE BREASTFED - Narendra, Yoga Hadi (Indonesian Journal of Community Health Nursing, 2025)
Introduction: According to transcultural nursing theory, universal and specific care approaches for people's health and wellbeing will be influenced by people's or groups' culture, values, beliefs, and practices. Infant mortality rates for babies who are not exclusively breastfed are high (IMR).Methods: Cross-sectional analysis was performed in this study. 289 respondents made up the study's sample size. Chi Square was used in the statistical analysis.Results: 64 respondents (22%), who placed a high priority on cultural norms and lifestyle, exclusively breastfed their infants. In contrast, 41 respondents (14%) did not exclusively breastfeed their infants.Conclusion: cultural negotiations will increase the rate of exclusive breastfeeding